1998
DOI: 10.1136/jnnp.65.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Shunt surgery in poor grade patients with tuberculous meningitis and hydrocephalus: effects of response to external ventricular drainage and other variables on long term outcome

Abstract: Thirty two poor grade patients (grade 3, 20 patients and grade 4, 12 patients) with tuberculous meningitis and hydrocephalus were prospectively studied to evaluate the response to external ventricular drainage in predicting outcome after shunt surgery. All grade 3 patients underwent a shunt procedure irrespective of their response to external ventricular drainage, and an attempt was made to correlate the immediate response to external ventricular drainage to their long term outcome. Patients in grade 4 underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 7 publications
(5 reference statements)
2
53
1
Order By: Relevance
“…Although some studies do not advocate surgical intervention among patients with a Vellore score of 4, there are also some studies showing benefit among these patients. [3,5,[10][11][12][13] Moreover, this study has also shown that an increase in the scores of eyeopening (E) and verbal output (V) components of the GCS score confers a multiplicative decrease in the probability of considering surgery. Higher E and V scores signify a better sensorium as seen in patients with a Vellore score of 1, where the majority of patients were given medical management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some studies do not advocate surgical intervention among patients with a Vellore score of 4, there are also some studies showing benefit among these patients. [3,5,[10][11][12][13] Moreover, this study has also shown that an increase in the scores of eyeopening (E) and verbal output (V) components of the GCS score confers a multiplicative decrease in the probability of considering surgery. Higher E and V scores signify a better sensorium as seen in patients with a Vellore score of 1, where the majority of patients were given medical management.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a Vellore score of 1-3 should be offered immediate surgery while Grade 4 may have a trial with an external ventricular drainage (EVD) first before having a shunt surgery to see if they would respond to it since these patients are already deemed to respond poorly to surgery. [3,5,[10][11][12][13] Moreover, CSF characteristics on lumbar tap were also chosen in the construction of the mathematical model since they are also found to be significant factors by other studies, especially the polymorphonuclear cell count, protein count, as well, the opening pressure (OP). [2,7,12] The other two commonly used parameters -radiographic evidence of the severity of hydrocephalus and the response to trial with an EVD -were not used in the development of our model since these are not commonly done in our institution.…”
Section: Symptoms Consistent With Hydrocephalus (Persistent Headache mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been stated that early ventricular shunting leads to a favorable outcome [4, 6, 8]; however, this has not been proven statistically. In fact, the studies performed on patients with TBM complicated by hydrocephalus are relatively few in number [5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. …”
Section: Introductionmentioning
confidence: 87%
“…Although shunt surgery has been recommended for the treatment of TBM with hydrocephalus, using this procedure in the treatment of hydrocephalus does not consistently result in favorable outcomes [5, 6]. …”
Section: Introductionmentioning
confidence: 99%